Hubungan Kematangan Emosi dengan Perilaku Bullying pada Siswa - Maria Isabela; Sitti Anggraini (Journal on Education, 2024)
This research aims to determine the relationship between emotional maturity and bullying behavior in students. This research is associative quantitative research. The sample in this study was 100 students taken using a purposive sampling method. The measuring tools for this research are an emotional maturity scale and a bullying behavior scale created by the researcher himself based on theory. The bullying behavior scale uses Sejiwa theory and the emotional maturity scale uses Walgito theory. The reliability of emotional maturity is 0.695 and the reliability of bullying behavior is 0.735. The results of this study show that there is no relationship between emotional maturity and bullying behavior in students with a significance level () of 0.446 (> 0.05), with a correlation of (-0.077).